Exploring EFL Students’ Attitudes toward British, American, and Indonesian English Accents at Tadulako University - Indah Maharani; Sriati Usman; Fadhilah Zamzam (Universitas Islam Negeri Palopo, 2026)
This study explores English as a Foreign Language (EFL) students’ attitudes toward British, American, and Indonesian English accents at Tadulako University, as well as the internal and external factors influencing their preferences. Employing a qualitative descriptive design, this research involved five undergraduate students from the English Education Study Program, with three selected for in-depth semi-structured interviews. Data were collected through informal observation, interviews, and field notes, and analyzed using thematic analysis based on Braun and Clarke’s framework. The findings reveal that students prioritize clarity and intelligibility as the most important characteristics of a good English accent, particularly in academic communication. While British and American accents are perceived as more fluent, prestigious, and associated with higher language proficiency, Indonesian English accent is valued for its familiarity and role in representing cultural identity. Additionally, students’ attitudes are shaped by social expectations, peer perceptions, and exposure to media, which often create pressure to adopt native-like accents. Despite this, participants generally recognize that effective communication does not require imitation of native speakers. This study highlights the complexity of students’ attitudes, which balance admiration for native accents with acceptance of local identity. It supports the perspective of English as an International Language (EIL), emphasizing intelligibility over native-like pronunciation. The findings suggest the importance of fostering inclusive language teaching practices that promote confidence, respect accent diversity, and prioritize communicative effectiveness in EFL classrooms.